2010
DOI: 10.1111/j.1095-8649.2010.02826.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of hatchery fish on wild populations in red sea bream Pagrus major (Perciformes, Sparidae) inferred from a partial sequence of mitochondrial DNA

Abstract: Variation in the mitochondrial DNA transcriptional control region sequence was investigated in wild and hatchery-released red sea bream Pagrus major from Kagoshima Bay, where an extensive hatchery-release programme has been conducted for >30 years. The programme has successfully augmented commercial catches in the bay (released juveniles have been produced from the captive broodstock, repeatedly used over multiple generations). Samples were also obtained from outside the bay, where limited stocking has occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
0
20
3
2
Order By: Relevance
“…A study of marine stock enhancement of red sea bream in Kagoshima Bay, Japan, reported losses of rare alleles and haplotypes even in the stocked population. In this instance, the wild stock was supplemented with hatchery fish produced from a domesticated broodstock over a 30-year period (Shishidou et al 2008;Kitada et al 2009;Hamasaki et al 2010). The JSM stock enhancement program has resulted in the release of 2 135 000 juvenile JSM (40-100 mm TL) in the SIS between 1998 and 2010 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A study of marine stock enhancement of red sea bream in Kagoshima Bay, Japan, reported losses of rare alleles and haplotypes even in the stocked population. In this instance, the wild stock was supplemented with hatchery fish produced from a domesticated broodstock over a 30-year period (Shishidou et al 2008;Kitada et al 2009;Hamasaki et al 2010). The JSM stock enhancement program has resulted in the release of 2 135 000 juvenile JSM (40-100 mm TL) in the SIS between 1998 and 2010 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, mismanagement of lobster fisheries in general should not mean that ventures aiming to enhance and conserve these fisheries via hatchery stocking should not be expected to pursue rigorous standards of ecological accountability. While stocking is generally expected to increase short-term abundance of populations, troubling recent data in other species suggest that negative genetic impacts may arise in target stocks, undermining fishery conservation objectives (Sekino et al, 2002(Sekino et al, , 2003Bert et al, 2007;Kitada et al, 2009;Rourke et al, 2009;Hamasaki et al, 2010;Christie et al, 2012a,b;Satake and Araki, 2012). It is increasingly apparent that the dual goals of short-term productivity and longterm conservation are not usually complementary and are difficult to achieve simultaneously (Satake and Araki, 2012).…”
Section: Ensuring Effective Genetic Managementmentioning
confidence: 99%
“…하지만 isozyme다형은 DNA상의 구조영역에 존재하여 생 물적 기능을 담당하는 부분이며 짧은 시간 내에 많은 시료를 처 리 할 수 있지만 조직 샘플시 조작이 어려우며, 단형적 유전자좌 (gene loci)가 많고 다형적 유전자좌일지라도 변이성이 떨어져 생 식격리 후의 시간이 짧은 지역집단간의 차이를 검출하는데는 한 계가 있다 (Brown et al, 1970;Park et al, 1993). 따라서 최근에 분자적 기술이 발전함에 따라 집단의 유전자 다양성을 평가하는 데 있어서 광범위하게 이용되고 있는 mtDNA와 msDNA 마커 등 (Taberlet and Bouvet, 1994;Kocher and Stepien, 1997), 특히 어류의 집단 유 전학 연구에 있어서 유용한 marker로 이용되고 있다 (Saito et al, 2008;Hamasaki et al, 2010). 그리고 msDNA마커는 핵DNA 염기 서열 상에서 2-6개의 염기가 반복적으로 나타나는 DNA로서 공우 성(codominant)으로 mtDNA에 비해 변이 정도가 크기 때문에 집 단유전학에서 강력한 유전자 마커로서 이용되어지고 있다 (Avise et al, 2000).…”
Section: 살오징어 성어는 산란을 위해 남하 회유하는데 암컷의 성숙은unclassified